ANALISIS RASIO KEUANGAN TERHADAP KELAYAKAN PEMBIAYAAN (STUDI KASUS PADA BMT EL-SEJAHTERA CIPARI CILACAP) - Imronah, ‘Ainul (Institut Agama Islam Bengkulu, 2017)
Many aspects are important in assessing the feasibility of financing. Financial Ratio analysis is one of important aspects in assessing the feasibility of financing. This analysis is needed to find out the company's financial performance so the development and the decline of a company is known and it is used as the tool of additional consideration by lks/creditors in making the decision to give or do not give the financing proposed by the company. The results showed that: banks implement and use the commonly existing theories in financial ratio analysis; performance assessment of companies is conducted by the bank based on the shape of the patterns of growth and decline of the company from year to year (trend); and the relevance of the conclusions made by the bank from the analysis results, relevant to what has been shown through analysis results itself. It can be concluded that the use of analysis financial ratios liquidity ratio analysis tool, the solvency ratio, the ratio of earning ratios, the ratio of the activity, and the ratio converge is in compliance with the existing theory, despite in certain periods the calculation development in few post is less significant. However, in another period of post can cover it. So, the company is deserved to get the financing.